Comparison of Parametric and Non-Parametric Estimation Methods in Linear Regression Model - Zaman, Tolga; Alakuş, Kamil (My University, 2019)
In this study, the aim was to review the methods of parametric and non-parametric analyses in simple linear regression model.The least squares estimator (LSE) in parametric analysis of the model, and Mood-Brown and Theil-Sen methods that estimatesthe parameters according to the median value in non-parametric analysis of the model are introduced. Also, various weights ofTheil-Sen method are examined and estimators are discussed. In an attempt to show the need for non-parametric methods,results are evaluated based on real life data.

Bu çalışmada, basit doğrusal regresyon modelinde parametrik ve parametrik olmayan analiz yöntemlerinin karşılaştırmalı olarakincelenmesi amaçlanmıştır. Modelin parametrik analizinde EKK tahmini, parametrik olmayan analizinde ise medyana göreparametre tahmini yapan Mood-Brown ve Theil-Sen yöntemleri tanıtılmıştır. Ayrıca Theil-Sen yöntemine ait çeşitli ağırlıklarincelenerek parametre tahmin ediciler tartışılmıştır. Parametrik olmayan yöntemlere olan ihtiyacı göstermek amacı ile sonuçlargerçek yaşam verisi üzerinde değerlendirilmiştir.
Doğrusal Regresyon Modelinde Parametrik ve Parametrik Olmayan Tahmin Yöntemlerinin Karşılaştırması
Keywords: \u0130statistik ve Olas\u0131l\u0131k; \u0130ktisat; \u0130\u015fletme